1986
DOI: 10.1095/biolreprod34.2.370
|View full text |Cite
|
Sign up to set email alerts
|

Puberty in Pine Voles, Microtus Pinetorum, and the Influence of Chemosignals on Female Reproduction1

Abstract: We investigated the reproductive biology of an induced ovulator, the pine vole (Microtus pinetorum). Male puberty, measured as age at first impregnation, was found to occur as early as 44 days of age. Female puberty measured as age at first conception, was found to occur as early as 32 days of age, considerably earlier than previously reported. Females paired with stud males exhibited a doubling of uterine weight within 12 h, and vaginal sperm were present after 48 h. This indicates that although behavioral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Termination of early gestation by novel (nonsire) males around the time of intrauterine blastocyst implantation (the Bruce effect; Bruce (1960)) and advancement of sexual maturation in nearby juvenile females (the Vandenbergh effect; Vandenbergh (1967)) have been extensively studied in mice and in a number of other mammals (e.g. Bronson & Eleftheriou 1963, Izard & Vandenbergh 1982, Drickamer 1983, Lepri & Vandenbergh 1986, Storey 1996. These phenomena share a number of qualities, especially their dependency upon male urinary constituents that bear upon the female's nasal area (Parkes & Bruce 1962, deCatanzaro et al 2006, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Termination of early gestation by novel (nonsire) males around the time of intrauterine blastocyst implantation (the Bruce effect; Bruce (1960)) and advancement of sexual maturation in nearby juvenile females (the Vandenbergh effect; Vandenbergh (1967)) have been extensively studied in mice and in a number of other mammals (e.g. Bronson & Eleftheriou 1963, Izard & Vandenbergh 1982, Drickamer 1983, Lepri & Vandenbergh 1986, Storey 1996. These phenomena share a number of qualities, especially their dependency upon male urinary constituents that bear upon the female's nasal area (Parkes & Bruce 1962, deCatanzaro et al 2006, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Lepri and Vandenbergh [25] found that as little as 12 h of contact with an adult male can result in a significant increase in uterine mass. When females were housed in wire-topped cages and males were housed directly overhead in wire-bottomed cages, there was a small but statistically significant increase in uterine mass.…”
Section: Introductionmentioning
confidence: 99%
“…When females were housed in wire-topped cages and males were housed directly overhead in wire-bottomed cages, there was a small but statistically significant increase in uterine mass. Lepri and Vandenbergh [25] suggested that exposure to excreta (urine or feces) led to estrogen secretion in young females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruce 1960, Vandenbergh 1967, Drickamer 1983. The Vandenbergh effect has also been observed in deer mice (Teague & Bradley 1978), voles (Lepri & Vandenbergh 1986), hamsters (Reasner & Johnston 1988), lemmings (Hasler & Banks 1975), opossums (Harder & Jackson 2003), pigs (Brooks & Cole 1970) and cows (Izard & Vandenbergh 1982). The Bruce effect has also been reported in deer mice (Bronson & Eleftheriou 1963), voles (Clulow & Langford 1971) and gerbils (Rohrbach 1982).…”
Section: Introductionmentioning
confidence: 91%